2018
DOI: 10.1161/hypertensionaha.117.10250
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Expression of RPS4Y1 (Ribosomal Protein S4, Y-Linked 1) Impairs STAT3 (Signal Transducer and Activator of Transcription 3) Signaling to Suppress Trophoblast Cell Migration and Invasion in Preeclampsia

Abstract: Normal placentation and a successful pregnancy depend on appropriate trophoblast cell migration and invasion. Inadequate trophoblast invasion and impaired spiral artery remodeling may lead to pregnancy-related disorders, such as preeclampsia. RPS4Y1 (ribosomal protein S4, Y-linked 1) is a member of the S4E family of ribosomal proteins. In this study, we found that RPS4Y1 levels were upregulated in placental samples collected from preeclamptic patients, when compared with the normotensive pregnant women. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…These findings suggest that STAT3 pathways play an important role in the pathogenesis of PE. Certain regulatory factors, such as RPS4Y1, HO-1, and HLA-G, have been reported to play a role in PE by affecting the expression and activation of STAT3 in trophoblast cells [20,34,35]. In the present study, we found that the STAT3 and p-STAT3 mRNA levels decreased following circPAPPA knockdown or miR-384 overexpression, and that this decrease could be reversed by co-transfection of miR-384 inhibitor and si-circPAPPA.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These findings suggest that STAT3 pathways play an important role in the pathogenesis of PE. Certain regulatory factors, such as RPS4Y1, HO-1, and HLA-G, have been reported to play a role in PE by affecting the expression and activation of STAT3 in trophoblast cells [20,34,35]. In the present study, we found that the STAT3 and p-STAT3 mRNA levels decreased following circPAPPA knockdown or miR-384 overexpression, and that this decrease could be reversed by co-transfection of miR-384 inhibitor and si-circPAPPA.…”
Section: Discussionsupporting
confidence: 57%
“…However, this process could also be partly reversed with the co-transfection of an miR-384 inhibitor and si-circPAPPA ( Figure 5D,E). The STAT3 pathway has been reported to be associated with PE, and studies have shown that STAT3 is a key regulator of trophoblast proliferation and invasion [19,20]. In addition, decreased expression and activation of STAT3 have been detected in PE patients [21].…”
Section: Examination Of the Role Of Regulation Of Circpappa And Mir-3mentioning
confidence: 99%
“…This analysis highlighted only one novel gene, RPS4Y1, which passed the preselected criterion of the significance of the association. RPS4Y1 is a member of the S4E family of ribosomal proteins, which promotes PE by impairing STAT3 (Signal Transducer and Activator of Transcription 3) signaling and suppressing migration and invasion of trophoblast cells (28). Figure 3B shows that the product of RPS4Y1 may also promote the development of ASD through the activation of multiple membrane proteins, including CD86, CD80, and CD83.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ribosomal protein S4 Y-linked 1 inhibits the migration and invasion of trophoblast cells in vitro and influences the growth of EVTs in villi placental explants by activating EMT-associated signaling pathways. 23 Our results showed that knockdown of RPL39 inhibited the proliferation, migration, and invasion of trophoblast cells in vitro. In addition, silencing RPL39 significantly suppressed the outgrowth capacity of EVTs in an ex vivo extravillous culture model.…”
Section: Discussionmentioning
confidence: 57%